Phase II study of TAS‐106 in patients with platinum‐failure recurrent or metastatic head and neck cancer and nasopharyngeal cancer. (18th April 2013) - Tsao, Anne; Hui, Edwin Pun; Juergens, Rosalyn; Marur, Shanthi; Huat, Tan Eng; Cher, Goh Boon; Hong, Ruey‐Long; Hong, Waun Ki; Chan, Anthony Tak‐Cheung
Abstract TAS‐106, a RNA polymerase inhibitor, was studied in solid tumors with potential clinical benefit and reasonable tolerability. We conducted a multicenter, international phase II trial of TAS‐106 in salvage metastatic or recurrent head and neck squamous cell cancer (HNSCC) and nasopharyngeal cancer (NPC) patients. TAS‐106 monotherapy was given at 6.5 mg/m2 over 24‐h continuous infusion every 3 weeks. Translational studies for blood and tissue were included. Twenty‐seven enrolled patients experienced the most common drug‐related adverse events of neutropenia, fatigue, non‐neutropenic fever, injection site reaction, and skin rash/dermatitis. The greater than or equal to grade 3 adverse events included neutropenia (14.8%), febrile neutropenia (7.4%), pneumonia (7.4%), and peripheral neuropathy (3.7%). The overall response rate was 0% in both subgroups; five HNSCC patients had stable disease (median duration 99 days) and four NPC patients had stable disease (median duration of 92.5 days). Median progression‐free survival (PFS) for HNSCC patients was 52 days (95% CI 43.0–99.0 days) and 48 days (95% CI 41.0–83.0 days) for NPC. Median overall survival (OS) for HNSCC patients was 175 days (95% CI 92.0–234.0 days) and 280 days (95% CI 107.0–462.0 days) for NPC. The TAS‐106 plasma levels were equivalent between Asian and Caucasian patients. There was no significant correlation of tumor UCK2 protein expression levels to TAS‐106 efficacy. TAS‐106 was reasonably tolerated in patients with platinum‐failure HNSCC and NPC. The administration schedule of 24‐h continuous infusion prevented neurologic toxicity, but had myelosuppression as its main toxicity. There was no anti‐tumor efficacy seen with TAS‐106 monotherapy. Future studies will focus on TAS‐106 combinations and mechanisms of drug resistance.